Formation and development of the Ukrainian legislation on criminal responsibility for insulting a military serviceman - Khramtsov, Olexandr (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2023)
The article examines the peculiarities of the formation and development of our country's legislation on criminal responsibility for insulting a military serviceman. The application of the historical method in this case made it possible to investigate the historical conditioning of the criminalization of such a socially dangerous act as an insult to a person in general and an insult to a military serviceman in particular. The studied legal monuments of the following periods: princely period; the period when Ukrainian lands were part of the Austro-Hungarian and Russian empires; the period of the Ukrainian SSR; the period of the independent state of Ukraine before the adoption of the new Criminal Code of Ukraine and the modern period.It is emphasized that the responsibility for an insult accrues a long time in the history of the legislation of our country. It contained norms on responsibility for the insult of any person, as well as for the insult of specifically defined persons: a woman, a mother, a father, a nobleman, etc. The insult was possible both by word and by physical actions. It was determined that for the first time the responsibility for insulting a serviceman was established by the Military Ordinance of Peter the I. The mentioned ordinance recognized only an officer (a special subject) as the subject of an insult. In the future, insult of various persons were criminalized: priests; officials; policemen, military personnel and others.Article 435-1 of the Criminal Code of Ukraine of 2001 fixed the composition of the insult of a serviceman in this form for the first time. And although disposition of the article causes certain remarks from scientists, practical workers and representatives of civil society, it is an important step in the criminal legal protection of the right of military personnel to professional honor and dignity. The author emphasizes that the criminalization of the insult of a military serviceman meets the conditions of historical conditionality and is timely and necessary.The article also provides author's definitions of the concepts of professional honor and dignity; criminal offense and its forms.